2021
DOI: 10.1038/s41467-021-23854-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for inhibition of the AAA-ATPase Drg1 by diazaborine

Abstract: The hexameric AAA-ATPase Drg1 is a key factor in eukaryotic ribosome biogenesis and initiates cytoplasmic maturation of the large ribosomal subunit by releasing the shuttling maturation factor Rlp24. Drg1 monomers contain two AAA-domains (D1 and D2) that act in a concerted manner. Rlp24 release is inhibited by the drug diazaborine which blocks ATP hydrolysis in D2. The mode of inhibition was unknown. Here we show the first cryo-EM structure of Drg1 revealing the inhibitory mechanism. Diazaborine forms a covale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Drg1 performs this function as a single protein. A recent study characterized the cryo-EM structure of Drg1 and suggested potential homology between this protein and SPATA5 ( Prattes et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Drg1 performs this function as a single protein. A recent study characterized the cryo-EM structure of Drg1 and suggested potential homology between this protein and SPATA5 ( Prattes et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the NIH clinical collection website, 446 small molecules have been registered that have already been used in clinical studies ( ) [ 61 ]. The drug diazaborine has been shown to bind with Drg1 and specifically block ATP hydrolysis, preventing Rlp24 release from pre-60S particles [ 62 , 63 ].…”
Section: Identification Of Inhibitors That Have Target Rrnamentioning
confidence: 99%
“… 16 ). The D2-domain-specific Drg1 inhibitor diazaborine therefore blocks Rlp24 extraction and prevents cell growth and proliferation 16 , 17 . The mechanism of Rlp24 release by Drg1 was unknown.…”
Section: Mainmentioning
confidence: 99%